ENHANCING ENGLISH VOCABULARY MASTERY THROUGH GAME-BASED APPROACHES FOR ELEMENTARY SCHOOL STUDENTS - Faida, Fardan Rezkiawan; Wijianto, Agung (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study aims to examine the impact of game-based learning, specifically through the use of Simon Says and Flashcards, on improving English vocabulary mastery among elementary school students. Vocabulary mastery is a crucial component of English proficiency that supports students’ ability to understand, speak, read, and write effectively. However, many elementary school students struggle to acquire sufficient vocabulary, leading to low motivation and learning outcomes. This research was conducted at SDN 12 Kendari, involving 26 fifth-grade students. A pre-experimental design with a pre-test and post-test model was implemented over five sessions, focusing on the themes “Body Parts” and “Things in the Classroom” through Simon Says and Flashcards activities. The pre-test average score was 23.65, which significantly increased to 72.58 in the post-test. The Wilcoxon Signed Ranks Test showed a significance value of 0.001 (< 0.05), indicating a statistically significant improvement. These findings demonstrate that game-based learning not only enhances students’ vocabulary mastery but also provides practical insights for teachers in designing engaging and collaborative classroom activities. This approach can be effectively applied to foster motivation and improve English language skills among elementary school students. ABSTRAK Penelitian ini bertujuan untuk melihat dampak pembelajaran berbasis permainan, khususnya menggunakan Simon Says dan Flashcards, terhadap peningkatan penguasaan kosakata bahasa Inggris pada siswa sekolah dasar. Kemampuan berbahasa Inggris, terutama penguasaan kosakata, sangat penting bagi siswa untuk dapat memahami, berbicara, membaca, dan menulis dalam bahasa Inggris. Namun, banyak siswa sekolah dasar mengalami kesulitan dalam menguasai kosakata, yang menyebabkan rendahnya motivasi dan hasil belajar. Penelitian ini dilaksanakan di SDN 12 Kendari dengan melibatkan 26 siswa kelas V. Desain penelitian yang digunakan adalah pra-eksperimental dengan model pre-test dan post-test selama lima kali pertemuan, menggunakan tema pembelajaran “anggota tubuh” dan “benda di kelas” melalui kegiatan Simon Says dan Flashcards. Hasil pre-test menunjukkan rata-rata 23,65, sedangkan post-test meningkat signifikan menjadi 72,58. Uji Wilcoxon Signed Ranks menghasilkan nilai signifikansi 0,001 (< 0,05), yang menunjukkan adanya peningkatan yang signifikan. Temuan ini menegaskan bahwa pembelajaran berbasis permainan tidak hanya efektif meningkatkan penguasaan kosakata, tetapi juga memberikan kontribusi bagi guru dalam menciptakan suasana belajar yang menyenangkan dan kolaboratif. Pendekatan ini dapat diterapkan secara luas untuk meningkatkan motivasi dan keterampilan berbahasa Inggris siswa sekolah dasar.